Transient thermal elastohydrodynamic simulation of a spiral bevel gear pair with an octoidal tooth profile under mixed friction conditions. (March 2020) - Bobach, Lars; Beilicke, Ronny; Bartel, Dirk
Abstract: A simulation model for the transient thermal elastohydrodynamic calculation of spiral bevel gears with octoidal toothing is presented. The three-dimensional contact geometry is derived directly from the precise geometrical definition of the tooth flank profiles. The tooth trace can be represented both as circular arc and as extended epicycloid. The simulation model is based on the numerical solution of the generalized Reynolds equation and includes models for mass conserving cavitation, non-Newtonian flow, mixed friction and microhydrodynamics. For the temperature calculation the energy equation for the fluid and the Fourier heat equation for the solid bodies are solved. Using the example of a spiral bevel gear pair with an extended epicycloid, the capability of the presented simulation model is shown. Highlights: Transient 3D-TEHL simulation model, to calculate tooth flank contacts in spiral bevel gear pairs with octoidal toothing. Derivation of the three-dimensional contact geometry directly from the geometrical definition of the tooth flank profiles. Representation of the tooth trace as circular arc or extended epicycloid. Incorporating mass conserving cavitation and non-Newtonian fluid behavior with limiting shear stress. Consideration of states of mixed friction and microhydrodynamics based on real measured surface topographies.